Coastal Inlet Analysis by Image Color Intensity Variations: Implications for the Barrier Coast of Ukraine - Ilya V. Buynevich; Oleksiy V. Davydov; Duncan M. FitzGerald (Journal of Marine Science and Engineering)
Inlets through coastal barriers in functionally non-tidal settings have been relatively understudied. Yet, they have morphosedimentary elements and morphodynamic behaviors that are similar to their tidal counterparts, especially microtidal (often wave-dominated) inlets. Increasingly, remote sensing technologies (aerial and satellite imagery, small unmanned aerial vehicles, etc.) are employed as sources of high-definition spatial databases. Such approaches are important in areas with limited access, especially in regions of military conflict, such as along parts of the northern Black Sea coast, Ukraine. For rapid spatial analysis of remotely sensed or archival datasets, image color intensity (ICI) patterns are obtained using grayscale (GS) spectra and a wide range of filter options. Areal and profile-style GS patterns based on relative ICI values are extracted from available imagery, so that in a full 256-value GS spectrum the deepest parts of a channel (inlet throat) will have the lowest (darkest) values (GS < 50). Landward (flood-tidal/bayside) and seaward (ebb-tidal/seaside) deltas will exhibit lighter colors (GS > 100). Exposed siliciclastic/carbonate sand-dominated barriers and shoals will yield the lightest values (GS > 200), with dark vegetation requiring GS inversion. Hypsometric information, as well as key metrics (perimeter and area) can be easily computed using instant tracing tools, without the need for labor-intensive contour outlining. This study is the first example of assessing cross-shore and longitudinal channel morphology of microtidal (USA) and non-tidal (Ukraine) inlets. The approach is also extended to a temporal analysis of inlet closure and a recent re-activation by an intense storm.